Hyperpolarized MRI theranostics in cancer - Yamashita, Koya; Zhao, Zhilei; Saito, Keita; Takakusagi, Yoichi (Frontiers in Oncology, 2025)
Hyperpolarized magnetic resonance imaging (MRI) has emerged as a transformative tool in cancer diagnostics, enabling real-time, non-invasive assessment of tumor metabolism. By employing hyperpolarized molecular probes, such as [1-13C]pyruvate, energy metabolism and metabolic changes associated with malignancy in tumors can be visualized, providing key insights into tumor aggressiveness, heterogeneity, and treatment response. In addition to their preclinical and clinical applications in cancer diagnostic imaging, some molecular probes can be used as potentiators of cancer therapy. This perspective article explores the potential use of hyperpolarized magnetic resonance spectroscopic imaging (MRSI) in conjunction with cancer treatment. Notably, the direct application of hyperpolarized molecular probes immediately after imaging to enhance DNA-targeted cancer therapies, including chemotherapeutic drugs and radiotherapy, is termed “hyperpolarized MRI theranostics in cancer.” In this novel approach, metabolic and physiological intratumoral changes induced by biomolecular probes are used to enhance the efficacy of subsequent therapeutic interventions. Additionally, future prospects for advancements in oncology enabled by hyperpolarized MRI are discussed.